Successful Knowledge Transfer from Universities of Applied Sciences in Germany Analysis of Best Practice Examples based on empirical analysis and expert interviews - Angelika Jager (European Regional Science Association (ERSA), 2011)
It is commonly accepted that universities are a source of new knowledge and an important part of innovation systems. Innovation and new knowledge are key drivers for regional economic growth and the economy of knowledge-based societies. Yet, regardless how prosperous universities' research establishments prove to be, success in terms of economic effects and economically successful application strongly depends on how effectively the gathered knowledge and created innovation is transferred to society, the industry, and innovation networks. Therefore, the organization and governance of knowledge transfer has become an important strategic issue for universities. In times of performance related allocation of funds, this holds especially true for German universities of applied sciences, as they are very dependent on contract research and successful knowledge transfer as a source of funding for research activities. The interface of research and application of knowledge offers high potential - both for success and failure. Several models of governance and support exist. Governments and universities invest millions in transfer departments with a diversity of jobs and tasks. Some financially encourage research and knowledge transfer in general. Others are convinced that only very successful establishments should be supported. Support can be organized centrally or peripheral in the university departments, in private companies or private-public-partnerships. The proposed paper investigates models of organizing and supporting knowledge transfer focusing on German universities of applied sciences. By developing a composition of important indicators and applying empirical analysis on nationwide databases, seven best practice examples are identified. Further best practices analysis is accomplished by online research, site and region inspection and expert interviews with the universities' representatives for knowledge transfer. The investigation proves that successful knowledge transfer depends on both internal and external factors. External factors often have strong influence and offer a high potential that needs to be realized, but can hardly be influenced. Analyzing the internal factors, it is underlined that no perfect way for organizing and managing knowledge transfer exists. But investigating the varying successful models, several conform features and interesting similarities can be identified.
Keywords: 330; Knowledge Transfer; German Universities of Applied Sciences; Best Practices Analysis